2018
DOI: 10.1016/j.molcel.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

MLKL Requires the Inositol Phosphate Code to Execute Necroptosis

Abstract: Necroptosis is an important form of lytic cell death triggered by injury and infection, but whether mixed lineage kinase domain-like (MLKL) is sufficient to execute this pathway is unknown. In a genetic selection for human cell mutants defective for MLKL-dependent necroptosis, we identified mutations in IPMK and ITPK1, which encode inositol phosphate (IP) kinases that regulate the IP code of soluble molecules. We show that IP kinases are essential for necroptosis triggered by death receptor activation, herpesv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
151
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 59 publications
18
151
2
1
Order By: Relevance
“…Cells with depletion of IP multikinase (IPMK) and inositol-tetrakisphosphate 1-kinase (ITPK1) which are critical for synthesis of cellular IPs were unable to show MLKL membrane association by necroptosis induction, despite the presence of phosphorylated MLKL. In IPMK and ITPK1 complemented cells, the membrane disruption and subsequent necroptosis were restored [70]. Thus, this indicates that IP kinases regulate necroptosis by influencing the plasma membrane association of phosphorylated MLKL.…”
Section: Mlkl Is the Effector Protein In Necroptosismentioning
confidence: 80%
“…Cells with depletion of IP multikinase (IPMK) and inositol-tetrakisphosphate 1-kinase (ITPK1) which are critical for synthesis of cellular IPs were unable to show MLKL membrane association by necroptosis induction, despite the presence of phosphorylated MLKL. In IPMK and ITPK1 complemented cells, the membrane disruption and subsequent necroptosis were restored [70]. Thus, this indicates that IP kinases regulate necroptosis by influencing the plasma membrane association of phosphorylated MLKL.…”
Section: Mlkl Is the Effector Protein In Necroptosismentioning
confidence: 80%
“…It is well-established that InsPs, such as InsP 3 (17) and InsP 4 (16,(18)(19)(20), act as signaling messengers in the activation of immune cells. However, little is understood about the roles of higher order InsPs in immune responses, although they can act as a structural cofactor or an allosteric regulator that modulates the stability and function of protein complex (21)(22)(23). Recently, it has been reported that a mixture of InsP 6 and Btk in solution might enable transient dimerization and transautophosphorylation of Btk (21).…”
mentioning
confidence: 99%
“…To undergo necroptosis, MLKL engagement requires the presence of specific lipids at the plasmatic membrane. Phosphatidyl inositol phosphates including, phosphatidylinositol-5-phosphate and phosphatidylinositol-4,5-bisphosphate have been described to function as lipid receptors of MLKL in the inner leaflet of the plasma membrane 5557 . These lipids are products of kinases that can phosphorylate the 3-, 4-, and 5-hydroxyl groups of the inositol head group of PI lipids 58 .…”
Section: Discussionmentioning
confidence: 99%